The roles of the state in the governance of socio-technical systems' transformation - Susana Borrás; Jakob Edler (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2020)
The transformative turn of innovation policy has resulted in calls for a more entrepreneurial and directional role of the state. However, the multiple roles that the state might play in such processes remain underexplored. This paper studies the embedded role of the state in four distinct modes of governance in socio-technical systems. Using a three-pillar analytical model, the paper examines four illustrative cases: cryptocurrencies, smart cities, automated vehicles, and nuclear power. The paper identifies 13 different roles of the state, indicating relevant variation across the four modes of governance. We discuss whether some roles of the state are more transformative than others, and provide clues for policy implications, and a future research agenda. The concept developed in the paper contributes to a more differentiated understanding of the transformative roles of the state.
urn:nbn:de:0011-n-5853962
Keywords: 330; Technologiepolitik; Innovation; Staatliche Einflussnahme; Sozialtechnologie; Virtuelle Währung; Stadt; Digitalisierung; Fahrerloses Transportsystem; Kernenergie